cGAMP/Saponin Adjuvant Combination Improves Protective Response to Influenza Vaccination by Microneedle Patch in an Aged Mouse Model - Vassilieva, Elena V.; Li, Song; Korniychuk, Heorhiy; Taylor, Dahnide M.; Wang, Shelly; Prausnitz, Mark R.; Compans, Richard W. (Frontiers in Immunology, 2021)
Current strategies for improving protective response to influenza vaccines during immunosenescence do not adequately protect individuals over 65 years of age. Here, we used an aged mouse model to investigate the potential of co-delivery of influenza vaccine with the recently identified combination of a saponin adjuvant Quil-A and an activator of the STING pathway, 2’3 cyclic guanosine monophosphate–adenosine monophosphate (cGAMP) via dissolving microneedle patches (MNPs) applied to skin. We demonstrate that synergy between the two adjuvant components is observed after their incorporation with H1N1 vaccine into MNPs as revealed by analysis of the immune responses in adult mice. Aged 21-month-old mice were found to be completely protected against live influenza challenge after vaccination with the MNPs adjuvanted with the Quil-A/cGAMP combination (5 µg each) and demonstrated significantly reduced morbidity compared to the observed responses in these mice vaccinated with unadjuvanted MNPs. Analysis of the lung lysates of the surviving aged mice post challenge revealed the lowest level of residual inflammation in the adjuvanted groups. We conclude that combining influenza vaccine with a STING pathway activator and saponin-based adjuvant in MNPs is a novel option for skin vaccination of the immunosenescent population, which is at high risk for influenza.